PERAN MASYARAKAT TERHADAP PERKEMBANGAN MORAL ANAK AKIBAT PERCERAIAN ORANG TUA DI KELURAHAN KAPUREN KEC. WLANTAKAN KOTA SERANG - Faujiah Faujiah; Ade Millatus Sa’adiyyah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
The Role of Society in the Moral Development of Children Due to Divorce Parents in Kapuren Village, Walantaka District, Serang City, Banten. Faculty of Teacher Training and Education, Pancasila and Citizenship Education, Banten Jaya University. This study aims to determine how the role of the community on children's moral development in the Kapuren Village. The subjects of this study are the Village Chief, Divorce Actors, Children and the Community. This researcher uses a qualitative method with a descriptive approach because to see the facts and conditions in the field that occur when the research takes place by presenting what actually happened. The results of this study indicate that there is still a lack of community's role in children's moral development due to parents' trust.